The effect of the addition of mangrove wood charcoal to reduce sulfur content in coal. Issue 1 (October 2020) - Rahman, R; Widodo, S; Azikin, B; Tahir, D
Abstract: Coal in Sulawesi, especially in South Sulawesi, has several shortcomings since it contains sulfur and produces a high ash content that affects the environment. Desulphurization with High-Temperature Combustion Methods is a sulfur content analysis method using the SC-144DR Dual Range Sulfur Analyzer coal tool, which is one of the methods used to reduce sulfur in coal. Based on the results of the study, it was obtained: a mixture of coal with mangrove wood charcoal with the composition of 25% Sin coal + 75% MWC = 0.067% sulfur content, 50% Sin coal + 50% MWC = 0.089% sulfur content and 75% Sin coal + 25% MWC = 0.107% sulfur content. These results indicate that the more addition of mangrove charcoal, the lower sulfur content in the coal. Decreasing sulfur content can improve the quality of the coal produced, especially in combustion systems that affect the environment.